Impressos que contam história(s) : considerações sobre as edições oitocentistas da obra O Hyssope, de António Diniz da Cruz e Silva - Andrezza Alves Velloso (2022)
Written in the late 1760s by António Diniz da Cruz e Silva (1731-1799), Hyssope was subject to censorship until it appeared in manuals and collections of Portuguese literature from the 19th century onwards. In the same century, the poem was republished several times, in Portugal and France, receiving, in each edition, an investment in images, explanatory notes and introductory texts. The present research focuses on these editions and seeks to understand the historical process of recognition of this work throughout the 1800s. To this end, the analysis focused on the editions produced between 1802 and 1879, as well as the contribution of figures such as Ferdinand Denis and Teófilo Braga to the significance of O Hyssope within the set of Portuguese Literature.